Mastering metasploit : exploit systems, cover your tracks, and bypass security controls with the Metasploit 5.0 framework /: exploit systems, cover your tracks, and bypass security controls with the Metasploit 5.0 framework. (2020) - Jaswal, Nipun
No abstract available